2022
DOI: 10.1155/2022/6107997
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Platelet-to-Albumin Ratio among Critically Ill Patients with Colorectal Cancer: A Propensity Score Matching Study

Abstract: The platelet-to-albumin ratio (PAR) was developed to evaluate inflammatory and nutritional status among patients. The primary goal of the current study was to gain insight into the prognostic role of PAR in critically ill patients with colorectal cancer (CRC). The secondary aim was to develop and verify a clinical model including PAR for the prediction of 28-day mortality. This observational, multicenter study used data from the Medical Information Mart for Intensive Care (MIMIC) IV, e-ICU databases, and Union… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Researchers have explored the prognostic utility of the PAR in human malignancies. Associations between high PARs and unfavorable survival outcomes have been reported among patients with colorectal cancer, locally advanced nasopharyngeal carcinoma, and juvenile osteosarcoma 21,22,29 . The PAR was reported to exhibit a stronger discriminative ability than did serum platelet counts and albumin levels alone 29 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Researchers have explored the prognostic utility of the PAR in human malignancies. Associations between high PARs and unfavorable survival outcomes have been reported among patients with colorectal cancer, locally advanced nasopharyngeal carcinoma, and juvenile osteosarcoma 21,22,29 . The PAR was reported to exhibit a stronger discriminative ability than did serum platelet counts and albumin levels alone 29 .…”
Section: Discussionmentioning
confidence: 97%
“…Associations between high PARs and unfavorable survival outcomes have been reported among patients with colorectal cancer, locally advanced nasopharyngeal carcinoma, and juvenile osteosarcoma. 21,22,29 The PAR was reported to exhibit a stronger discriminative ability than did serum platelet counts and albumin levels alone. 29 Considering the effects of factors such as infection and chronic hepatic dysfunction on serum platelet counts and albumin levels, 30 the PAR, which combines both parameters, may offer reduced measurement variability and enhance reliability when compared to using either parameter alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al [23] found that NAR had a good predictive role for the postoperative prognosis of CRC patients. Li et al [28] considered that PAR was a reliable indicator for predicting the short-term survival outcome of critically ill CRC patients. Our study results showed that NPRI, NLR, NAR, and PAR could well predict the short-term and long-term prognosis of patients undergoing laparoscopic radical resection for CRC, but NLR, NAR, and PAR were not independent risk factors for postoperative prognosis in CRC patients.…”
Section: Discussionmentioning
confidence: 99%